Probing the Action of Cytochrome c Oxidase - Daskalakis, Vangelis; Varotsis, Constantinos (My University, 2014)
Density functional theory (DFT) and combined Molecular Mechanics/Quantum Mechanics (MM/QM-MD) calculations have been applied to models of the cytochrome c oxidase (CcO) including the Fe–CuB binuclear center, where dioxygen is bound and subsequently reduced to water. The properties of several intermediates of the CcO dioxygen reaction have been investigated by theoretical approaches. In this chapter, we investigate the dynamics of the binuclear heme Fe–CuB throughout the O2 catalytic cycle. We are focused on the effects of the protein matrix and proton/water motion exerted on the heme a 3 group. For this, we have built models of CcO, which vary at the heme a 3 environment. This variability is based on hydrogen bonding interactions and amino acid protonation states. Different control points have been identified for the transition from one intermediate to the next. The hydrogen bonding networks in the proximity of heme a 3 area also have consequences for the characteristics of the binuclear center. A theoretical framework for the direct link between an H+ delivery channel (termed D) and an accumulation of waters, termed ‘water pool’ close to the active site, has been achieved at the QM/MM level of theory. Two proton valves (E278 and His403) and an electron/proton coupling site (propionate-A/Asp399) exist in this pathway for the aa 3 CcO from P. denitrificans. The ferryl intermediate, produced subsequent to the O–O bond scission, is found to have characteristics highly dependent on the basicity of the proximal His411, in contrast to the hydroxyl intermediate that is sensitive to distal effects.
Keywords: Cell Physiology; Protein Structure; Microbiology; Bacteriology